2011
DOI: 10.1007/s00120-011-2635-2
|View full text |Cite
|
Sign up to set email alerts
|

Onkologische und funktionelle Ergebnisse der offenen intrafaszialen radikalen Prostatektomie

Abstract: The goal of the study is to critically analyze both the functional and especially the oncological results, which should not be compromised by the nerve-sparing approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…Until now, the intrafascial nerve-sparing technique has been a technique of very advanced surgeons. 9,10,[17][18][19][20][21][22][23][24] In the intrafascial nerve-sparing ELRP, the dissection of the prostate was performed between the prostatic capsule and the prostatic fascia and left virtually no periprostatic tissue overlying the prostate. Theoretically, this approach may lead to a higher incidence of PSM due to a dissection that is closer to the prostate gland.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, the intrafascial nerve-sparing technique has been a technique of very advanced surgeons. 9,10,[17][18][19][20][21][22][23][24] In the intrafascial nerve-sparing ELRP, the dissection of the prostate was performed between the prostatic capsule and the prostatic fascia and left virtually no periprostatic tissue overlying the prostate. Theoretically, this approach may lead to a higher incidence of PSM due to a dissection that is closer to the prostate gland.…”
Section: Discussionmentioning
confidence: 99%
“…Potdevin et al 17 found that there was a high rate of PSM in patients with pT3 disease who underwent the intrafascial nerve-sparing technique during robotassisted laparoscopic radical prostatectomy. However, Shikanov et al 18 , Neill et al 19 and Khoder et al 20 reported that the bilateral interfascial nerve-sparing technique does not result in higher rates of PSM in low-risk patients.…”
Section: Discussionmentioning
confidence: 99%